1988
DOI: 10.1530/acta.0.1190373
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoantibodies in thyroid cancer: Incidence and relationship with tumour outcome

Abstract: In the present investigation we studied serum anti-thyroglobulin and anti-thyroid microsomal autoantibodies, measured by hemagglutination technique, in 600 patients with thyroid cancer seen by us from 1975 to 1985 (mean follow-up 46 months). Positive thyroglobulin antibodies and/or microsomal antibodies were found in 138 (23%) patients (23.9% with papillary, 25% with follicular, 16.1% with anaplastic, and 4.1% with medullary thyroid carcinomas). The incidence of positive tests was similar in each decade of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(72 citation statements)
references
References 9 publications
7
58
0
4
Order By: Relevance
“…The use of TgAbs as a prognostic parameter in DTC remains controversial. While Rubello et al (18) and Adil et al (12) reported a higher frequency of relapse in association with persisting TgAbs after ablative therapy, the majority of authors (1,8,10,11) found no correlation, in agreement with our data. …”
Section: Prevalence and Development Of Tgabs In Dtc Patientssupporting
confidence: 91%
“…The use of TgAbs as a prognostic parameter in DTC remains controversial. While Rubello et al (18) and Adil et al (12) reported a higher frequency of relapse in association with persisting TgAbs after ablative therapy, the majority of authors (1,8,10,11) found no correlation, in agreement with our data. …”
Section: Prevalence and Development Of Tgabs In Dtc Patientssupporting
confidence: 91%
“…A ntithyroglobulin antibodies (anti-TgAbs) are detectable in about 20-25% of patients with thyroid cancer (TC) (1,2). These antibodies interfere with measurement of thyroglobulin (Tg), the key biomarker used to detect and monitor thyroid cancer (2).…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies interfere with measurement of thyroglobulin (Tg), the key biomarker used to detect and monitor thyroid cancer (2). Tg is generally measured using immunometric assays (IMA) or radioimmunoassay (RIA), with the former being more commonly used in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The concept that total thyroid ablation reduces thyroid autoimmune phenomena is supported by the observation that total thyroidectomy followed by radioiodine therapy is associated with a progressive decrease and disappearance of circulating autoantibodies in initially antibody-positive thyroid cancer patients who are diseasefree after treatment 87 . Therefore, also in the case of GO, total antigen deprivation and autoreactive T-lymphocyte depletion might prove beneficial for eye disease 88 .…”
Section: Total Thyroid Ablationmentioning
confidence: 99%